UPAYA PEMBELAJARAN SEJARAH DALAM MEMBENTUK KARAKTER TECHNOPRENEURSHIP BERBASIS KEARIFAN LOKAL - Regina Permatadewi; Herdin Muhtarom; Tubagus Umar Syarif Hadi Wibowo (Universitas Bina Bangsa, 2021)
Education has an important role in shaping character and developing the potential contained in students. Education as a reference for instilling character values ​​so that students can implement character values ​​through their potential. One of the characters that can be developed in the world of education is the character of technopreneurship. The character of techopreneurship emphasizes the collaborative process between technological advances and entrepreneurial skills. The role of history learning can be used as a way to shape the character of technoprenurship. By learning history, students or students can develop skills that combine aspects of technology, entrepreneurship and historical values, so that the next generation of the nation has the potential to develop technopreneurshi characters, not forgetting local wisdom and the nation's historical values. The research method used is qualitative research through a literature study approach. The purpose of the research is to provide preventive efforts in preserving the historical value and local wisdom in Indonesia, especially in Banten and developing technopreneurship to promote history and local wisdom to the general public